p62/SQSTM1 promotes rapid ubiquitin conjugation to target proteins after endosome rupture during xenophagy - Megumi Tsuchiya; Hidesato Ogawa; Takako Koujin; Chie Mori; Hiroko Osakada; Shouhei Kobayashi; Yasushi Hiraoka; Tokuko Haraguchi (FEBS Open Bio)
Autophagy is a bulk degradation pathway, and selective autophagy to remove foreign entities is called xenophagy. The conjugation of ubiquitin to target pathogens is an important process in xenophagy but when and where this ubiquitination occurs remains unclear. Here, we analyzed the temporal sequence and subcellular location of ubiquitination during xenophagy using time‐lapse observations, with polystyrene beads mimicking invading pathogens. Results revealed accumulation of a ubiquitination marker around the beads within 3 min after endosome rupture. Recruitment of ubiquitin to the beads was significantly delayed in p62‐knockout murine embryonic fibroblast cells, and this delay was rescued by ectopic p62 expression. Ectopic expression of a phosphorylation‐mimicking p62 mutated at serine residue 405 (equivalent to human serine residue 403) rescued this delay, but its unphosphorylated form did not. These results indicate that ubiquitination mainly occurs after endosome rupture and suggest that p62, specifically the phosphorylated form, promotes ubiquitin conjugation to target proteins in xenophagy.